Controlled Growth and Reliable Thickness‐Dependent Properties of Organic–Inorganic Perovskite Platelet Crystal. (25th May 2016) - Niu, Lin; Zeng, Qingsheng; Shi, Jia; Cong, Chunxiao; Wu, Chunyang; Liu, Fucai; Zhou, Jiadong; Fu, Wei; Fu, Qundong; Jin, Chuanhong; Yu, Ting; Liu, Xinfeng; et al.
Abstract : Organolead halide perovskites (e.g., CH3 NH3 PbI3 ) have caught tremendous attention for their excellent optoelectronic properties and applications, especially as the active material for solar cells. Perovskite crystal quality and dimension is crucial for the fabrication of high‐performance optoelectronic and photovoltaic devices. Herein the controlled synthesis of organolead halide perovskite CH3 NH3 PbI3 nanoplatelets on SiO2 /Si substrates is investigated via a convenient two‐step vapor transport deposition technique. The thickness and size of the perovskite can be well‐controlled from few‐layers to hundred nanometers by altering the synthesis time and temperature. Raman characterizations reveal that the evolutions of Raman peaks are sensitive to the thickness. Furthermore, from the time‐resolved photoluminescence measurements, the best optoelectronic performance of the perovskite platelet is attributed with thickness of ≈30 nm to its dominant longest lifetime (≈4.5 ns) of perovskite excitons, which means lower surface traps or defects. This work supplies an alternative to the synthesis of high‐quality organic perovskite and their possible optoelectronic applications with the most suitable materials. Abstract : High‐quality organic–inorganic perovskite nanoplatelets can be well‐controlled synthesized from few‐layers to hundred nanometers on Si/SiO2 substrate. Raman characterizations reveal that the evolutions of Raman peaks are sensitive to the thickness. Furthermore, under the thickness‐dependent photoresponse and time‐resolved photoluminescence measurements of perovskite devices, the results indicate the most suitable thickness for their possible optoelectronic applications.